2009
DOI: 10.1364/oe.17.005580
|View full text |Cite
|
Sign up to set email alerts
|

Dissipative soliton resonance in an all-normaldispersion erbium-doped fiber laser

Abstract: We report on the generation of 281.2 nJ mode locked pulses directly from an erbium-doped fiber laser mode-locked with the nonlinear polarization rotation technique. We show that apart from the conventional dissipative soliton operation, an all-normal-dispersion fiber laser can also emit square-profile dissipative solitons whose energy could increase to a very large value without pulse breaking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
140
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 327 publications
(151 citation statements)
references
References 11 publications
9
140
0
2
Order By: Relevance
“…This means that the generated pulse is highly-chirped in agreement with the all-normal-dispersion nonlinear dynamics studied recently for mode-locked fibre lasers with standard cavity lengths [13][14][15][16][17][18][19][20][21]. Note that no special narrow band filter limiting laser radiation spectrum was used in a stable mode-locked operation, unlike the regimes reported in [16,19].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This means that the generated pulse is highly-chirped in agreement with the all-normal-dispersion nonlinear dynamics studied recently for mode-locked fibre lasers with standard cavity lengths [13][14][15][16][17][18][19][20][21]. Note that no special narrow band filter limiting laser radiation spectrum was used in a stable mode-locked operation, unlike the regimes reported in [16,19].…”
Section: Discussionsupporting
confidence: 80%
“…However, intensity is limited by the soliton conditions and too high intensity of radiation leads to the generation of multiple solitons and their nonregular interactions in the presence of noise. Recently it was revealed that the mode locking of fibre lasers can also be achieved in the normal dispersion regime [13][14][15][16][17][18][19][20]. The recently discovered all normal dispersion generation regime is based on the interplay of the cavity dispersion, the Kerr nonlinearity and the gain.…”
mentioning
confidence: 99%
“…It has the same terms as that found by the method of moments (see Equation (10) in [7]). Thanks to collective variable approach, we have found a simple analytic expression for the resonance curve which is in good qualitative agreement with in [7].…”
Section: Resonance Curve From a Collective Variable Approachmentioning
confidence: 76%
“…Despite of its superior robustness, passive mode-locking is a dissipative process involving composite mechanisms and effects, e.g., nonlinearity, dispersion, loss and gain [12]. Such a complex system, indeed, is an ideal platform for nonlinear physics study, which has gained its popularity in the past few years, e.g., optical rogue wave generation [13][14][15][16][17], soliton explosion [18,19], soliton rain [20], and soliton resonance [21][22][23][24]. Therein, the randomly-arranged multiple pulses arising from peak power clamping [25], on the other hand, make the control and understanding of nonlinear physics involved in the passive mode-locking more difficult.…”
Section: Introductionmentioning
confidence: 99%